Benefits of psychological counseling for employees - Nguyen, Thu Ngan; Černá, Daniela; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The objective of this thesis is to provide the reader with a better understanding of workplace counseling, the benefits that result from it, how it might impact job satisfaction and the downsides of it as well. The theoretical part reviews literature on Human Resources and job satisfaction, mental health, the Covid-19 impact, and workplace counseling. The practical part of the thesis analyses the data that has been collected in the form of quantitative research. Data collection took place in the form of a distributed questionnaire mainly among Czech employees through the snowball sampling technique. The objective was to observe how Covid-19 impacted respondents’ mental health and to discover their views on workplace counseling. The contribution of this work lies in the proposal of implementation of workplace counseling in the Czech Republic which could lead to improvements in employees’ mental well-being, higher job satisfaction, and even protection of organizations from litigation.
Vedoucí práce: Daniela Černá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses